A pivotal role of GSK-3 in synaptic plasticity - Bradley, Clarrisa A.; Peineau, Stephane; Taghibiglou, Changiz; Nicolas, Celine S.; Whitcomb, Daniel J.; Bortolotto, Zuner A.; Kaang, Bong-Kiun; Cho, Kwangwook; Wang, Yu-Tian; Collingridge, Graham L. (Frontiers in Molecular Neuroscience, 2012)
Glycogen synthase kinase-3 (GSK-3) has many cellular functions. Recent evidence suggests that it plays a key role in certain types of synaptic plasticity, in particular a form of long-term depression (LTD) that is induced by the synaptic activation of N-methyl-D-aspartate (NMDA) receptors. In the present article we summarise what is currently known concerning the roles of GSK-3 in synaptic plasticity at both glutamatergic and GABAergic synapses. We summarise its role in cognition and speculate on how alterations in the synaptic functioning of GSK-3 may be a major factor in certain neurodegenerative disorders.